Sustainability of public finances and automatic stabilisation under a rule of budgetary discipline - José M. Marín (European Central Bank (ECB), 2002)
This paper addresses the question of how a fiscal rule of a general type can preserve the sustainability of public finances and provide automatic stabilisation, taking as given interest rates and price stability. This issue can be considered complementary to the analysis of monetary policy rules, whose targets are price stability and often also output stabilisation, assuming that fiscal policy guarantees the sustainability of public finances. Considering the institutional framework provided by the Stability and Growth Pact, the paper also draws some policy conclusions.
Keywords: E61; H62; H63; 330